Characterisation of avocado and asparagus farms in the Chavimochic irrigation project in La Libertad, Peru - Apaza, W. (2019)
The Chavimochic irrigation project is one of the leading projects in Peru. In this project, irrigation water is derived from the Santa river to irrigate the valleys of Chao, Viru, and Moche, including desert zones between valleys. In this study, we aimed to characterise the Hass avocado and asparagus farms in desert areas of the Chavimochic irrigation project. Social, economic and environmental information was collected through structured surveys of 12 asparagus and 17 avocado farms. Four groups of asparagus farms and three groups of avocado farms were identified based on principal component and cluster analyses. Profitability of the avocado crop was higher than that of the asparagus crop, and irrigation caused more significant variability in the crop yield of avocado than that of asparagus. From the social perspective, the income of farm personnel was related to the level of education, and female personnel showed more participation in the Chavimochic irrigation project than in other agroecosystems of Peru.